PRODUCTIVITY OF BEAN-CEREAL GRASSES DEPENDING ON THE ELEMENTS OF GROWING TECHNOLOGY - Пророченко, Тетяна; Ільченко, Яна; Бурко, Леся; Свистунова, Ірина (SWorldJournal, 2022)
The results of research on the influence of species composition of grass mixtures, the level of fertilizing, and growth stimulator Fumar on the productivity of sown meadow herbage on typical low-humus chernozems of the Right-Bank Forest-Steppe are present